Orbital Myositis: A Comprehensive Review and Reclassification - McNab, Alan A (Ophthalmic plastic and reconstructive surgery, 2020)
Orbital myositis occurs in typical and atypical forms. This review summarizes and updates the current state of knowledge of all forms of inflammation affecting extraocular muscle, excluding thyroid-associated orbitopathy. A comprehensive literature review of orbital myositis was performed. Orbital myositis typically occurs in an idiopathic acute form, with painful diplopia due to inflammation in 1 or more extraocular muscles of young adult females, which usually responds to a course of oral corticosteroids. Atypical forms include idiopathic chronic or recurrent orbital myositis, and myositis related to systemic autoimmune, inflammatory, and infective conditions. The commonest associated autoimmune condition is inflammatory bowel disease. Immunoglobulin G4-related ophthalmic disease often affects extraocular muscle. Drug reactions and rarely paraneoplastic disease may also cause extraocular muscle inflammation. Orbital myositis occurs in a typical acute steroid responsive form, but atypical forms related to specific autoimmune and inflammatory conditions are increasingly recognized. Orbital myositis has many similarities to uveitis and would benefit from a systematic approach to nomenclature, diagnosis, and treatment.